1997
DOI: 10.1136/oem.54.10.734
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for carpal tunnel syndrome in a general population.

Abstract: (Occup Environ Med 1997;54:734-740)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
1
11

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(108 citation statements)
references
References 25 publications
8
88
1
11
Order By: Relevance
“…The studies on flexion or extension of the wrist show large differences in exposure levels that are already associated with an increased occurrence of CTS, as was found for three case-control studies. Nordstrom et al (52) presented an increased risk of CTS with bending the wrist for >3 hours/day, Blanc et al (58) reported hand bending >2 hours/day as a risk factor, whereas, in the study of De Krom et al (43), the risk was already elevated when the wrist was extended or flexed for 1 hour/ week. These results, all based on self-reported exposure, are too contradictory for drawing any meaningful conclusion about harmful exposure levels.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The studies on flexion or extension of the wrist show large differences in exposure levels that are already associated with an increased occurrence of CTS, as was found for three case-control studies. Nordstrom et al (52) presented an increased risk of CTS with bending the wrist for >3 hours/day, Blanc et al (58) reported hand bending >2 hours/day as a risk factor, whereas, in the study of De Krom et al (43), the risk was already elevated when the wrist was extended or flexed for 1 hour/ week. These results, all based on self-reported exposure, are too contradictory for drawing any meaningful conclusion about harmful exposure levels.…”
Section: Discussionmentioning
confidence: 96%
“…Three articles reported a significant association between exposure to vibration and CTS, with OR values of 2.52 to 4.8 (46,51,52). An increased risk of CTS was found for workers using vibrating tools (1-20 years and >20 years) and power tools or machinery (6-11 hours/day) (46,52). In the cross-sectional study of Bovenzi et al (51), 8-hour time-weighted exposures of 4.7 m/s 2 and 3.9 m/s 2 to hand-arm vibration were associated with CTS.…”
Section: Exposure and Carpal Tunnel Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Carpal tunnel syndrome is commonly seen with occupations that require repetitive tasks involving the hand and wrist, including mouse use, keyboarding, painting, and jobs with similar duties. Although repetitive stress has been well documented as the mechanism of injury for CTS, 27,28 other factors may predispose a patient to injury. These factors include a squarer anatomical configuration of the wrist and carpal tunnel, 29 and wrist angles maintained at greater than 20°of extension while typing.…”
Section: Introductionmentioning
confidence: 99%
“…Nordstrom et al [37] found the risk of CTS increased 8% for each unit of increase in BMI (about 6 lbs.). Nathan and Keniston summarized that being overweight, older, and physically inactive are major risk factors for slowing (of the median nerve) and clinical CTS [33].…”
Section: Epidemiology Of Carpal Tunnel Syndrome and Sleep Disturbancesmentioning
confidence: 99%